Tardigrades, Water Bears, Moss Piglets Tardigrada (Spallanzani 1777) - Carrie Suen; Jennifer Lynn Gillett-Kaufman (EDIS, 2021)
Tardigrades, commonly known as water bears, are a type of microscopic animal found across a vast array of moist and aquatic environments. Tardigrades are known for their extensive resilience due to the fact that they are also found in extreme environments such as Antarctica, deep sea vents, and mud volcanoes. They are commonly used as a model organism for scientific research.